OBSTETRIC MANAGEMENT OUTCOMES OF PATIENTS WITH GESTATIONAL DIABETES MELLITUS DELIVERING AFTER 34 WEEKS AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITA (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluation of obstetric outcomes in patients with gestational diabetes mellitus who delivered after 34 weeks at Nghe An Obstetrics and Pediatrics Hospital.Subjects and Methods: A cross-sectional descriptive study based on the medical records of 150 patients with gestational diabetes mellitus who delivered after 34 weeks at Nghe An Obstetrics and Pediatrics Hospital from January 1, 2022 to December 31, 2023.Results: Most patients were older than 25 years, and 46% had a history of previous cesarean delivery. A total of 96.7% of gestational diabetes mellitus (GDM) cases were delivered by cesarean section, primarily due to a prior cesarean section (38.62%) and complications of GDM (macrosomia, abnormal fetal presentation or amniotic fluid abnormalities, etc.). The mean neonatal birth weight was 2770 g, and Apgar scores were favorable, ranging from 7 to 10 in more than 94% of cases. Respiratory distress and hypoglycemia were the two most common neonatal complications, accounting for 6% and 3.3%, respectively.Conclusions: Cesarean delivery was the predominant mode of delivery among patients with gestational diabetes mellitus, accounting for 96.7% of cases. Most neonates had a birth weight around 2,500 g with favorable Apgar scores ranging from 7 to 10. The most common neonatal complications were respiratory distress and hypoglycemia.